Substrate and stereocontrolled iodocycloetherification of highly functionalized enantiomerically pure allylic alcohols: application to synthesis of cytotoxic 2-epi jaspine B and its biological evaluation1. Issue 30 (14th August 2015) - Kundooru, Somireddy; Das, Pintu; Meena, Sanjeev; Kumar, Vikash; Siddiqi, Mohammad Imran; Datta, Dipak; Shaw, Arun K.
<x xml:space="preserve">Abstract</x> A mechanistic study on iodocycloetherification of enantiopure allylic alcohols is established. Its application to synthesis of marine cytotoxic 2-epi jaspine B has been demonstrated.